Dangerous But Not Omnipotent Exploring the Reach and Limitations of Iranian Power in the Middle East - Wehrey, Frederic (RAND Corporation, 2009)
In an analysis grounded in the observation that although Iranian power projection is marked by strengths, it also has serious liabilities and limitations, this report surveys the nature of both in four critical areas and offers a new U.S. policy paradigm that seeks to manage the challenges Iran presents through the exploitation of regional barriers to its power and sources of caution in the regime?s strategic calculus.